Question #d2c06

1 Answer
Sep 7, 2017

Answer:

  1. #x = 4#
  2. #x>6.25#
  3. #x=-10#
  4. ...
  5. #-2x^2+3x+9#
  6. ..

Explanation:

  • #3*x+5 = 17#
    To solve these of equations, the unknown, #x#, has to be isolated one side of the equation,
    First, we subtract 5 from both side of the equation to get rid of the 5 on the left side.
    #3*x +5 -5 = 17 -5#
    #3*x = 12#

Then divide by 3 both sides
#(3*x)/3 = 12/3#
#x = 4#
(3 by 3 cancel out, and 12/3=4)

  • #4*x- 5>20#

Same as before, add 5 to both sides of the equation
#4*x- 5+5>20+5#
#4*x>25#

divide by 4 both sides of the equation
#(4*x)/4>25/4#
#x>6 1/4#
#x>6.25#

  • #2-x=12#
    subtract 2 from both sides of the equation
    #2-x-2=12-2#
    #-x=10#
    since x is negative, we have to multiply both sides by -1
    #(-x)(-1)=(10)(-1)#
    #x=-10#

  • 4th try it yourself

  • #(2x+3)(3-x)#
    in these kind of equations, you have to multiply each term of the first with the each terms of the second,
    it is written as #(ax+b)*(cx+d)#
    and it is equal to
    #(ax)(cx)+(b)(cx)+(ax)(d)+(b)(d)#

in the one in your example,
#(2x+3)(3-x)#
is equal to
#(2x)(-x)+(3)(-x)+(2x)(3)+(3)(3)=-2x^2+(-3x)+6x+9#
simplifying the answer by adding #-3x+6x=3x#
Therefore, the answer is
=#-2x^2+3x+9#

  • Last one give it a try

If you could not solve the 4th and the last I will help you with them.
I Hope that this will help. :)